2019
DOI: 10.1002/jemt.23243
|View full text |Cite
|
Sign up to set email alerts
|

Silver release of Ag (I) doped hydroxyapatite: In vitro study

Abstract: A material is produced by doping of silver (Ag (I)) which has antibacterial property to nano hydroxyapatite (nHAp), to remove the hipersensitivity in the teeth by closing the dentine tubules or dental micro cracks of the teeth and effective against for some bacteria. The doping of Ag (I) can also produces a toxic effect. Ag (I) can be released from the structure as a result of biological, physical and chemical effects and may cause toxicity. Therefore, it is important to determine whether the presence of Ag (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The presence of Ag + also contributed to lower corrosion rates of the samples compared to pure HA [45]. Additionally, the pH value, which varied between 6.55 and 7.40 in all measurements for the Ag + -doped HA groups, was suitable for the living system [46].…”
Section: Ag + -Doped Ha-based Materialsmentioning
confidence: 89%
“…The presence of Ag + also contributed to lower corrosion rates of the samples compared to pure HA [45]. Additionally, the pH value, which varied between 6.55 and 7.40 in all measurements for the Ag + -doped HA groups, was suitable for the living system [46].…”
Section: Ag + -Doped Ha-based Materialsmentioning
confidence: 89%
“…In addition, it is suggested that hydroxyapatite coatings containing fluoride, silver, etc. ions on implants can effectively inhibit bacterial adhesion and growth without affecting the activity of osteoblasts and epithelial cells (23)(24)(25). The cell study results obtained from the product in question help to conclude that hydroxyapatite will be an effective dental treatment material when its known antibacterial properties are considered.…”
Section: Cytotoxicity Assaymentioning
confidence: 97%